(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the phraseological units that are of fundamental importance in the Uzbek linguistics, and their semantic structure is one of the important features of the lexical richness of the language. There are many methods and techniques for studying phraseological units. In particular, the structural-typological method, variational method, contextological method, complex method and other similar methods are very important in the study of phraseological units. The article contains stable phrases in all languages, and uses them to discuss the meaning of ideas in speech. Some Persian idioms and their Uzbek alternatives will also be discussed.